(untitled) (Global Journal of Management and Business Research, 2020)
Background: Business ethics is the doorbell in management literature and for business houses today. The essence of human values is quite pertinent for long term sustenance of organizations. Understanding business ethics and its relevance in recent times is the most calling global challenge across organizations. The objective of the study is to explore and investigate the prominent domains and items that may be considered on the relevance, applicability and rationale of business ethics viz. Domain A: Employee Goals for Business Ethics, Domain B: Diversity Management, Domain C: Entity Value on Decision making, Domain D: Legal Perspectives of Business, E: Diversified Ethics with Gender Differentiation. The paper ultimately aims towards developing a scale for finding conclusive remarks in certain identifiable areas within the field of Business Ethics. The main source of conceptualizing the domains is formulated with related literature and the Experts opinion comprising both academicians and practicing managers in the industry in Kolkata as well as across the country through primary and secondary collection methods.